Introduction to development economics - Ghatak, Subrata (Routledge, 2003)
The fourth edition of this classic textbook introduces students to the vital field of development economics. With vastly improved and updated pedagogical features, Subrata Ghatak introduces what can be a difficult topic with a welcome clarity.